2010
DOI: 10.1242/jcs.068924
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Rb by PCAF is required for nuclear localization and keratinocyte differentiation

Abstract: SummaryAlthough the retinoblastoma protein (Rb) functions as a checkpoint in the cell cycle, it also regulates differentiation. It has recently been shown that Rb is acetylated during differentiation; however, the role of this modification has not been identified. Depletion of Rb levels with short hairpin RNA resulted in inhibition of human keratinocyte differentiation, delayed cell cycle exit and allowed cell cycle re-entry. Restoration of Rb levels rescued defects in differentiation and cell cycle exit and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 39 publications
4
50
0
Order By: Relevance
“…2B). 26 Although the reason for altered subcellular localization in GT198 variants has not been clear, a similar cytoplasmic localization is well observed in splice variant or mutant forms of tumor suppressors such as p53, 20,36,37 Rb, 38 or BRCA1. 12 The ability to stimulate transcription, induce apoptosis, and impair Rad51 foci formation minimally suggests that GT198 variants are functionally effective.…”
Section: Gt198 Splice Variants Antagonize Wild-type Activitiesmentioning
confidence: 81%
“…2B). 26 Although the reason for altered subcellular localization in GT198 variants has not been clear, a similar cytoplasmic localization is well observed in splice variant or mutant forms of tumor suppressors such as p53, 20,36,37 Rb, 38 or BRCA1. 12 The ability to stimulate transcription, induce apoptosis, and impair Rad51 foci formation minimally suggests that GT198 variants are functionally effective.…”
Section: Gt198 Splice Variants Antagonize Wild-type Activitiesmentioning
confidence: 81%
“…We demonstrated that knockdown of Pkd1 in mouse IMCD3 cells with 2 different lentiviruses expressing shRNAs increased not only SIRT1 expression (Figure 1C), but also Rb phosphorylation ( Figure 8A), compared with To support the functional relationship between SIRT1 and Rb in renal epithelial cells, we found that SIRT1 interacted with Rb by demonstrating that anti-Rb antibody could pull down SIRT1 ( Figure 8D). Due to the lack of antibodies for acetyl-Rb, we used anti-Rb antibody to pull down Rb and subsequently used an anti-acetyl-α-lysine antibody to evaluate the acetylation of Rb, as performed by other laboratories (24,25). We found that acetylated Rb was decreased in SIRT1 upregulating Pkd1-null MEK versus WT MEK cells ( Figure 8D).…”
Section: Pc1 Affects Sirt1 Expression In Renal Epithelial Cells Throumentioning
confidence: 90%
“…Another possibility is that K111 acetylation favors E2 retention within the nucleus. Notably, it was recently proposed that pCAF-mediated acetylation of lysines within the NLS of the retinoblastoma proteins promotes its nuclear retention (65). This scenario can be envisioned by the entry of E2 into a macromolecular KAT complex that prevents its loss to the cytosol.…”
Section: Discussionmentioning
confidence: 99%